Web Content Processing Method for Electronic Business Systems - Vysotska, Victoria; Chyrun, Lyubomyr (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The given article is devoted to the development of standardized methods and software Web content processing in e-business systems. The model of electronic content commerce systems is developed. The models of commercial Web content processing subsystems are constructed. A new approach of business processes application and implementation for the construction of electronic content commerce systems is formulated. Complex methods of formation, management and support commercial content are developed. Software for information resources processing in electronic content commerce systems is developed. The methods of e-business systems designing and implementation are presented as example on online newspaper and online magazine that reflect the theoretical studies results.